Effect of crude ethanolic seed extract from Mucuna pruriens on proliferation, apoptosis, and cell cycle arrest in gastric adenocarcinoma (AGS) cells - Arulvasu Chinnasamy; Vennila Jayaprakash; Deepakrajasekar Padmanaban; Niranjni Sekar; Rajasekar Valayapathi; Aarthi Azhagudurai; Sumathi Ethiraj (SpringerOpen, 2024)
Abstract Background Gastric cancer is a prevalent form of malignancy among many common carcinoma cases globally. This study was designed to assess the anticancer potential of the crude ethanolic seed extract from Mucuna pruriens against the gastric cancer cell line (AGS). Various assays were employed to assess the anticancer properties, including examinations of cell viability, nuclear morphology, apoptosis using AO/EB staining, changes in mitochondrial membrane potential, lactate dehydrogenase activity, DNA fragmentation, and cell cycle arrest. Results The crude extract exhibited significant anticancer activity against the human gastric cancer cell line (AGS), as determined by the MTT assay, with an inhibition concentration (IC50) of 600 µg/mL at 24 h. Distinct cellular and nuclear morphological changes were observed with different concentrations of crude ethanolic seed extract. The LDH release assay reveals cell death in AGS cells, as evidenced by a significant increase in the release of LDH enzyme. DNA fragmentation analysis and flow cytometry results indicate that the extract induces chromatin condensation, apoptotic cell death, and cell cycle arrest at the G0/G1 phase in the AGS cancer cell line. These results highlight the potential therapeutic advantages of Mucuna pruriens seed extract against gastric cancer cells. Conclusion This study could pave the way for identifying diverse natural bioactive compounds sourced from Mucuna pruriens seed, leading to the development of novel drug with potential anticancer properties.